European company law 1999-2010: renaissance and crisis - Armour, John; Ringe, Wolf-Georg (Brussels, 2011)
"European corporate law has enjoyed a renaissance in the past decade. Fifteen years ago, this would have seemed most implausible. In the mid-1990s, the early integration strategy of seeking to harmonise substantive company law seemed to have been stalled by the need to reconcile fundamental differences in approaches to corporate governance. Little was happening, and the grand vision of the early pioneers appeared more dream than ambition. Yet since then, a combination of adventurous decisions by the Court of Justice, innovative approaches to legislation by the Commission, and disastrous crises in capital markets has produced a headlong rush of reform activity. The volume and pace of change has been such that few have had time to digest it: not least policymakers, with the consequence that the developments have not always been well coordinated. The recent 2007/08 financial crisis has yet again thrown many - quite fundamental - issues into question. In this article, we offer an overview that puts the most significant developments of this decade into context, alongside each other and the changing patterns of corporate structure in European countries."